THE QTC INTERVAL AND TREATMENT OUTCOME OF INPATIENTS WITH COVID-19 - Jovanovic, Jovan Bozidar; Jankovic, Slobodan M.; Zdravkovic, Natasa; Davidovic, Goran; Veselinovic, Mirjana; Canovic, Petar; Zaric, Milan; Sazdanovic, Maja; Sazdanovic, Predrag; Pantic, Katarina; Cekerevac, Ivan; Folic, Marko M.; et al. (PONS - medicinski časopis, 2022)
Background: After the beginning of the COVID-19 pandemic caused by the SARS-CoV -2 virus, enormous pressure fell on the entire health system. Since there is no adequate cure for this disease, "off-label" use of several drugs (azithromycin, chloroquine, hydroxychloroquine, etc.) was resorted to. The aim of this study was to analyse QTc interval dynamics and its relationship with other factors which could influence outcome in patients with COVID-19.Methods: Study has observational, case-control design with retrospective data collection from medical files of adult patients, with RT-PCR confirmed COVID-19. The cases (n=30) were subjects with fatal outcome and the controls (n=169) were the survivors. The QTc interval was calculated on admission, during and after initial drug treatments with presumed activity against SARS-CoV-2, mostly antimalarials. Primary independent and outcome variables were QTc interval prolongation and all-cause mortality, respectively.Results: Study population included 120 males (60.3%), the mean patients’ agewas 57.3±15.8 years (±SD). The most common comorbid illnesses were hypertension (98 patients), pre-existing arrhythmias (32) and diabetes mellitus (29). The most frequently prescribed QTc prolonging drugs were azithromycin (69.8% of patients), chloroquine (50.3%) and hydroxychloroquine (42.7%). Total of 131 patients (65.8%) had QTc interval increase >60 ms from baseline, of whom 5 had QTc prolongation >500 ms (2.5%). De novo ventricular tachyarrhythmias were registered at 14 patients (7%) and 13 (92.8%) of them died. Pre-existing arrhythmias (odds ratio 9.30, 95% confidence interval 2.91-29.73, p
Keywords: coronavirus; pandemics; pneumonia, viral; inpatients; antimalarials; long QT syndrome; treatment outcome